Fluoride ion battery and manufacturing method thereof
The integration of Cu-based active material with BiF3 in the positive electrode layer of fluoride ion batteries addresses the issue of particle coarsening, resulting in improved capacity and energy density by ensuring complete fluorination reactions at lower temperatures.
Patent Information
- Application Number
- JP2021085187
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-05-20
AI Technical Summary
Copper (Cu) used as a positive electrode active material in fluoride ion batteries tends to aggregate and become coarse during charging and discharging, leading to incomplete fluorination reactions and insufficient capacity characteristics.
A fluoride ion battery with a positive electrode active material layer containing Cu-based active material and BiF3, where the molar ratio of Cu to Bi is between 1 and 3, and the average particle size of Cu is 100 nm or less, with BiF3 acting as a coarsening prevention material.
The battery achieves improved capacity characteristics by suppressing particle coarsening and ensuring smooth fluorination and defluorination reactions, even at lower temperatures, thereby enhancing energy density.
Smart Images

Figure 0007608966000002 
Figure 0007608966000003 
Figure 0007608966000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to fluoride ion batteries and methods of making the same. [Background technology]
[0002] For example, Li-ion batteries are known as high-voltage and high-energy density batteries. Li-ion batteries are cation-based batteries that utilize the reaction between Li ions and a positive electrode active material and the reaction between Li ions and a negative electrode active material. On the other hand, fluoride-ion batteries that utilize the reaction of fluoride ions (fluoride anions) are known as anion-based batteries. For example, Patent Document 1 discloses a fluoride-ion battery that uses a positive electrode active material having an active material containing at least one of Ag, Co, Mn, Cu, W, and V, and a fluoride that coats the active material. [Prior art documents] [Non-patent literature]
[0003] [Patent Document 1] JP 2018-063905 A Summary of the Invention [Problem to be solved by the invention]
[0004] Copper (Cu), which is used as the positive electrode active material in fluoride ion batteries, has the advantage that it is easy to improve the energy density because it is capable of two-electron reactions. However, Cu tends to aggregate and become coarse during charging and discharging, so the fluorination reaction does not progress to the inside during charging, and sufficient capacity characteristics may not be obtained.
[0005] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide a fluoride ion battery having good capacity characteristics. [Means for solving the problem]
[0006] In the present disclosure, a Cu-based active material and BiF 3 The present invention provides a fluoride ion battery comprising a positive electrode active material layer containing
[0007] According to the present disclosure, the positive electrode active material layer is made of a Cu-based active material and BiF 3 Since the fluoride-ion battery contains the fluoride, the capacity characteristics of the battery are excellent.
[0008] In the above disclosure, the positive electrode active material layer is characterized in that the Cu-based active material is the BiF 3 The composite particles may be coated with
[0009] In the above disclosure, the molar ratio of Cu to Bi (Cu / Bi) in the positive electrode active material layer may be 1 or more and 3 or less.
[0010] In the above disclosure, the Cu-based active material may contain Cu as a main component of the metal element.
[0011] In the above disclosure, the Cu-based active material may further contain F.
[0012] In the above disclosure, the Cu-based active material may have an average particle size of 100 nm or less.
[0013] In addition, the present disclosure includes a precursor layer forming step of forming a precursor layer containing a Cu-based active material and Bi, and a method of introducing fluoride ions into the precursor layer to form a Cu-based active material and a BiF 3 and forming a positive electrode active material layer containing the above-mentioned.
[0014] According to the present disclosure, Cu-based active materials and BiF 3 Since the positive electrode active material contains the above, a fluoride ion battery having good capacity characteristics can be obtained. Effect of the Invention
[0015] The present disclosure has an effect of providing a fluoride ion battery with good capacity characteristics. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating a fluoride ion battery according to the present disclosure. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating a fluoride ion battery according to the present disclosure. [Diagram 3] FIG. 1 is an explanatory diagram for explaining a problem of Cu. [Figure 4] FIG. 2 is a schematic cross-sectional view illustrating the relationship between a Cu-based active material and BiF 3 in a positive electrode active material layer. [Diagram 5] 1A to 1C are schematic cross-sectional views illustrating a method for manufacturing a fluoride ion battery in the present disclosure. [Figure 6] 1 shows the results of TEM-EDX measurement of the CuBi nanoparticles (before the first charge) obtained in Example 1. [Figure 7] 1 shows the results of TEM-EDX measurement of the CuBi nanoparticles (after the first charge) obtained in Example 1. [Figure 8] 4 shows the results of a charge / discharge test on the evaluation cell obtained in Example 1. [Figure 9] 4 shows the results of a charge / discharge test on the evaluation cell obtained in Comparative Example 1. [Figure 10] 1 shows the results of a charge / discharge test on the evaluation cell obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The fluoride ion battery and the manufacturing method thereof according to the present disclosure will be described in detail below.
[0018] A. Fluoride-ion battery Fig. 1 is a schematic cross-sectional view illustrating a fluoride ion battery according to the present disclosure. The fluoride ion battery 10 shown in Fig. 1 has a positive electrode active material layer 1, a negative electrode active material layer 2, an electrolyte layer 3 disposed between the positive electrode active material layer 1 and the negative electrode active material layer 2, a positive electrode current collector 4 that collects current from the positive electrode active material layer 1, and a negative electrode current collector 5 that collects current from the negative electrode active material layer 2. In the present disclosure, the positive electrode active material layer 1 is made of a Cu-based active material and BiF 3 The present invention contains at least the following:
[0019] FIG. 2 is a schematic cross-sectional view illustrating a fluoride ion battery according to the present disclosure, showing a battery in which a negative electrode active material layer is formed by itself upon charging. The fluoride ion battery 10 shown in FIG. 2(a) does not have a negative electrode active material layer between the electrolyte layer 3 and the negative electrode current collector 5, and the electrolyte layer 3 and the negative electrode current collector 5 are in direct contact with each other. The electrolyte layer 3 is a solid electrolyte that contains a metal fluoride (e.g., Pb 2-x Sn x F 4 2(a), during the initial charge, a defluorination reaction of the metal fluoride occurs at the interface between the electrolyte layer 3 and the negative electrode current collector 5, producing a negative electrode active material (e.g., Pb). As a result, a negative electrode active material layer 2 is self-formed as shown in FIG. 2(b).
[0020] According to the present disclosure, the positive electrode active material layer is made of a Cu-based active material and BiF 3 As mentioned above, copper (Cu), which is used as the positive electrode active material of fluoride ion batteries, is capable of two-electron reactions (two electrons reacting with one Cu), which has the advantage that it is easy to improve the energy density. On the other hand, when Cu is fluorinated, it becomes CuF 2 is generated, but CuF 2 does not have electronic conductivity and has low fluoride ion conductivity. Therefore, as shown in Figure 3, if the particle size of Cu is large, the fluorination reaction does not progress to the inside during charging. Therefore, it is preferable that the particle size of Cu is small, and it is particularly preferable that it is nano-sized.
[0021] In addition, Cu tends to aggregate and become coarse during charging and discharging. 2 In this case, the volume expands to a maximum of 1.5 times, but when the expanded Cu particles come into contact with each other, they are thought to change into spherical lumps in order to reduce the surface tension. Therefore, even if nano-sized Cu is used, if coarsening occurs, the fluorination reaction will not progress to the inside during charging. In contrast, in the present disclosure, BiF 3 The presence of fluoride can suppress the coarsening of particles, resulting in a fluoride-ion battery with good capacity characteristics.
[0022] BiF 3 The reason why the presence of BiF suppresses particle coarsening is that 3 It is speculated that the presence of BiF reduces the frequency of contact between Cu particles. 3 CuF 2 Since the fluoride ion conductivity of Bi is higher than that of Cu, even when the reaction temperature is low, the charge and discharge proceeds smoothly and the capacity characteristics are improved. That is, the fluoride ion battery of the present disclosure has an advantage that the capacity characteristics are good at a relatively low temperature (for example, 60° C.). In addition, since the fluorination / defluorination potential of Bi is lower than the fluorination / defluorination potential of Cu, when Cu functions as an active material, BiF 3 In addition, because Bi can exist stably as a single element, it has the advantage that it is easy to synthesize CuBi nanoparticles, which will be described later.
[0023] 1.Cathode active material layer The positive electrode active material layer in the present disclosure is made of a Cu-based active material and BiF 3 The layer contains Cu. The Cu-based active material contains at least Cu. The Cu-based active material may contain only Cu as a metal element, or may contain other metals in addition to Cu. Examples of other metals include alkali metals, alkaline earth metals, transition metals, and lanthanoid metals. The Cu-based active material may contain Pb or may not contain Pb.
[0024] The Cu-based active material preferably contains Cu as the main component of the metal element. "Contains Cu as the main component of the metal element" means that the molar ratio of Cu is the largest among all the metal elements in the Cu-based active material. The ratio of Cu to all the metal elements in the Cu-based active material may be, for example, 50 mol% or more, 70 mol% or more, or 90 mol% or more. The ratio of the metal elements in the Cu-based active material can be confirmed, for example, by performing high-frequency inductively coupled plasma (ICP) emission spectroscopy.
[0025] The Cu-based active material may or may not contain F. The Cu-based active material is, for example, CuF x (0≦x≦2), where x varies depending on the SOC (state of charge) of the fluoride-ion battery.
[0026] The shape of the Cu-based active material is preferably particulate. 50 ) is, for example, 100 nm or less, and may be 65 nm or less. If the average particle size of the Cu-based active material is too large, the fluorination reaction does not progress to the inside during charging, and there is a possibility that sufficient capacity characteristics will not be exhibited. On the other hand, the average particle size (D 50 ) is, for example, 10 nm or more, and may be 20 nm or more. If the average particle size of the Cu-based active material is too small, it may be difficult to manufacture it. 50 ) can be measured, for example, by observation with a scanning electron microscope (SEM) (for example, n≧100). It can also be calculated from the measured value of the BET specific surface area. 2 In this case, the volume expands to a maximum of 1.5 times. Taking this into consideration, the average particle size (D 50 ) is preferably, for example, 65 nm or less.
[0027] The content of the Cu-based active material in the positive electrode active material layer is, for example, 30% by weight or more, may be 50% by weight or more, or may be 70% by weight or more.
[0028] BiF 3 Generally, BiF functions as a material to prevent the coarsening of Cu-based active materials. For example, as shown in FIG. 4(a), 3 The positive electrode active material layer may be coated with a Cu-based active material. 3 The surface of the Cu-based active material may contain a composite particle coated with BiF. 3 The coverage of BiF is, for example, 20% or more, may be 50% or more, or may be 70% or more. 3 The coverage of the BiF in the composite particles may be 100%. Methods for measuring the coverage include, for example, transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). 3 The average thickness of the BiF in the composite particles is, for example, 0.5 nm or more, may be 1 nm or more, or may be 10 nm or more. 3 The average thickness of BiF is, for example, 30 nm or less, and may be 20 nm or less. 3 The average thickness can be measured, for example, by a transmission electron microscope (TEM).
[0029] On the other hand, as shown in Fig. 4(b), for example, 3 and the Cu-based active material may be particles. That is, the positive electrode active material layer may be composed of particles of the Cu-based active material and BiF 3 and particles of BiF 3 The average particle size (X) of the particles is preferably smaller than the average particle size (Y) of the particles of the Cu-based active material. 3 This is because the particles are easily arranged in the matrix. The ratio of X to Y (X / Y) is, for example, 0.5 or less, may be 0.3 or less, or may be 0.1 or less.
[0030] The molar ratio of Cu to Bi in the positive electrode active material layer is Cu / Bi. Cu / Bi is not particularly limited, but may be, for example, 0.1 or more, and may be 1 or more. If Cu / Bi is too small, the proportion of the Cu-based active material is relatively small, and the volume energy density may be low. On the other hand, the value of Cu / Bi may be, for example, 10 or less, and may be 3 or less. If Cu / Bi is too large, the coarsening of the Cu-based active material may not be sufficiently suppressed. When the positive electrode active material layer contains the above-mentioned composite particles, Cu / Bi is preferably 1 or more and 3 or less.
[0031] The positive electrode active material layer may contain a conductive material. The addition of the conductive material improves the electronic conductivity of the positive electrode active material layer. Examples of the conductive material include carbon materials. Examples of the carbon material include carbon black such as acetylene black, ketjen black, furnace black, and thermal black, graphene, fullerene, and carbon nanotubes.
[0032] The proportion of the conductive material in the positive electrode active material layer is, for example, 1% by weight or more, and may be 5% by weight or more. If the proportion of the conductive material is too small, there is a possibility that a good electron conduction path is not formed. On the other hand, the proportion of the conductive material in the positive electrode active material layer is, for example, 20% by weight or less, and may be 15% by weight or less. If the proportion of the conductive material is too high, the proportion of the positive electrode active material becomes relatively small, and the energy density may decrease.
[0033] The positive electrode active material layer may contain an electrolyte. The addition of the electrolyte improves the ionic conductivity of the positive electrode active material layer. The electrolyte may be a solid electrolyte or a liquid electrolyte (electrolytic solution). The electrolyte is the same as that described in "2. Electrolyte Layer" below. The positive electrode active material layer may contain a binder. Examples of the binder include fluorine-based binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). The thickness of the positive electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.
[0034] 2. Electrolyte layer The electrolyte layer in the present disclosure is a layer disposed on the side of the positive electrode active material layer opposite to the positive electrode current collector. The electrolyte contained in the electrolyte layer may be a solid electrolyte or a liquid electrolyte (electrolytic solution).
[0035] The solid electrolyte may be, for example, an inorganic solid electrolyte containing a metal element and a fluorine element. The inorganic solid electrolyte may contain only one metal element, or may contain two or more metal elements. The inorganic solid electrolyte may be, for example, a fluoride containing a lanthanoid element such as La or Ce, a fluoride containing an alkali metal element such as Li, Na, K, Rb, or Cs, or a fluoride containing an alkaline earth element such as Ca, Sr, or Ba.
[0036] The inorganic solid electrolyte is preferably a fluoride containing at least one of La, Ba, Pb, Sn, Ca and Ce. 1-x Ba x F 3-x (0≦x≦1), Pb 2-x Sn x F 4 (0≦x≦2), Ca 2-x Ba x F 4 (0≦x≦2), Ce 1-x Ba x F 3-x (0≦x≦1). Each of the x's may be greater than 0, 0.3 or greater, 0.5 or greater, or 0.9 or greater. Each of the x's may be smaller than 1, 0.9 or less, 0.5 or less, or 0.3 or less. The shape of the inorganic solid electrolyte may be, for example, particulate.
[0037] The electrolyte contains, for example, a fluoride salt and a solvent. Examples of the fluoride salt include inorganic fluoride salts, organic fluoride salts, and ionic liquids. Examples of the inorganic fluoride salt include XF (X is Li, Na, K, Rb, or Cs). Examples of the cation of the organic fluoride salt include alkyl ammonium cations such as tetramethylammonium cations. The concentration of the fluoride salt in the electrolyte is, for example, 0.1 mol / L or more and 6 mol / L or less.
[0038] The solvent may be, for example, R 1 -O(CH 2 CH 2 O) n -R 2 (R 1 and R 2 are each independently an alkyl group having 4 or less carbon atoms or a fluoroalkyl group having 4 or less carbon atoms, and n is within a range of 2 to 10), cyclic carbonates such as ethylene carbonate (EC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), propylene carbonate (PC), and butylene carbonate (BC), and chain carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The electrolytic solution may contain an alkali metal amide salt.
[0039] 3.Negative electrode active material layer The negative electrode active material layer in the present disclosure is a layer containing at least a negative electrode active material, and may further contain at least one of a conductive material, a binder, and an electrolyte.
[0040] Examples of the negative electrode active material include a metal element, an alloy, a metal oxide, and a fluoride thereof. Examples of the metal element contained in the negative electrode active material include La, Ca, Al, Eu, Li, Si, Ge, Sn, In, V, Cd, Cr, Fe, Zn, Ga, Ti, Nb, Mn, Yb, Zr, Sm, Ce, Mg, and Pb.
[0041] In addition, as the negative electrode active material, carbon materials such as graphite, coke, and carbon nanotubes, and polymer materials such as polyaniline, polypyrrole, polyacetylene, and polythiophene can also be used. As for the conductive material, electrolyte, and binder, the same materials as those described in "1. Positive electrode active material layer" above can be used.
[0042] As described above, in the present disclosure, the negative electrode active material layer may be self-formed by a defluorination reaction of the solid electrolyte contained in the electrolyte layer. The thickness of the negative electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.
[0043] 4.Other configurations The fluoride ion battery in the present disclosure may have a positive electrode current collector that collects the current of the positive electrode active material layer, and a negative electrode current collector that collects the current of the negative electrode active material layer. The positive electrode current collector and the negative electrode current collector may have, for example, a foil shape, a mesh shape, or a porous shape. The fluoride ion battery may also have a separator between the positive electrode active material layer and the negative electrode active material layer. By providing a separator, a safer battery can be obtained.
[0044] 5. Fluoride-ion batteries The fluoride ion battery in the present disclosure may be a primary battery or a secondary battery, but is preferably a secondary battery, since it can be repeatedly charged and discharged and is useful, for example, as a battery for use in a vehicle. In addition, the shape of the fluoride ion battery in the present disclosure may be, for example, a coin type, a laminate type, a cylindrical type, or a square type.
[0045] B. How Fluoride-Ion Batteries are Made FIG. 5 is a schematic cross-sectional view illustrating a method for manufacturing a fluoride ion battery according to the present disclosure. In the method for manufacturing a fluoride ion battery shown in FIG. 5, first, an intermediate structure 11 having a precursor layer 1X containing a Cu-based active material and Bi is produced (FIG. 5(a)). The precursor layer 1X contains, for example, composite particles in which a Cu-based active material is coated with Bi. The intermediate structure 11 also has a negative electrode active material layer 2, an electrolyte layer 3, a positive electrode current collector 4, and a negative electrode current collector 5 in addition to the precursor layer 1X. Next, the intermediate structure 11 is charged to introduce fluoride ions into the precursor layer 1X, and the Cu-based active material and BiF 3 A positive electrode active material layer 1 containing the above is formed, thereby obtaining a fluoride ion battery 10 (FIG. 5(b)).
[0046] According to the present disclosure, Cu-based active materials and BiF 3 In particular, when the precursor layer contains composite particles in which the Cu-based active material is coated with Bi, the Bi is fluorinated after the preparation of the precursor layer to obtain BiF 3 By creating BiF 3 Damage to the coating can be suppressed. For example, if the Cu-based active material is already BiF 3 When composite particles coated with BiF were used, the positive electrode active material layer was prepared. 3 The coat may be damaged by collision with other materials (e.g., conductive materials). To address this issue, Bi is fluorinated after the preparation of the precursor layer to form BiF 3 By creating BiF 3 Damage to the coat can be reduced.
[0047] 1. Precursor layer formation process The precursor layer forming step in the present disclosure is a step of forming a precursor layer containing a Cu-based active material and Bi.
[0048] The precursor layer contains a Cu-based active material and Bi. The precursor layer may contain composite particles in which the Cu-based active material is coated with Bi. The composite particles in the precursor layer forming step usually do not contain fluorine. For example, a method of synthesizing the composite particles may include a method of subjecting a mixture of a Cu-based active material and simple Bi to a thermal plasma treatment. The precursor layer may also contain particles of a Cu-based active material and Bi particles. The value of Cu / Bi, the average particle size of the Cu-based active material, and other matters are the same as those described in "A. Fluoride ion battery" above.
[0049] The precursor layer may further contain at least one of a conductive material, a binder, and an electrolyte, as described above in "A. Fluoride ion battery."
[0050] In addition, the present disclosure can also provide a method for producing the above-mentioned composite particles, which includes a thermal plasma treatment step of performing a thermal plasma treatment on a mixture of a Cu-based active material and Bi (Bi alone). In addition, the present disclosure can also provide composite particles in which a Cu-based active material is covered with Bi (Bi alone). The coverage of Bi on the surface of the Cu-based active material is, for example, 20% or more, may be 50% or more, or may be 70% or more. On the other hand, the coverage of Bi may be 100%. The average thickness of Bi in the composite particles is, for example, 0.5 nm or more, may be 1 nm or more, or may be 10 nm or more. On the other hand, the average thickness of Bi in the composite particles is, for example, 30 nm or less, or may be 20 nm or less.
[0051] 2. Positive electrode active material layer formation process The positive electrode active material layer forming step is a step of introducing fluoride ions into the precursor layer to form a Cu-based active material and a BiF 3 and forming a positive electrode active material layer containing the above.
[0052] Comparing Cu and Bi, the fluorination potential of Bi is lower than that of Cu, so during charging, the fluorination reaction of Bi occurs first, and then the fluorination reaction of Cu occurs. On the other hand, during discharging, the defluorination reaction of Cu occurs, but the defluorination reaction of Bi does not occur.
[0053] The method of introducing fluoride ions into the precursor layer is not particularly limited, but includes a method of preparing a chargeable intermediate structure and performing a charging process. The intermediate structure may be a fluoride ion battery before the first charge, as shown in FIG. 5(a), for example. The charging conditions are not particularly limited, and are set so that at least a fluorination reaction of Bi occurs. The Cu-based active material in the positive electrode active material layer may or may not contain F. The positive electrode active material layer obtained by this process is the same as that described in "A. Fluoride ion battery" above.
[0054] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0055] [Example 1] (Synthesis of CuBi nanoparticles) CuBi nanoparticles were synthesized using a thermal plasma method with Cu powder and Bi powder as raw materials. The Cu / Bi molar ratio was set to 2.66. The surfaces of the CuBi nanoparticles were measured by TEM-EDX. The results are shown in Figures 6(a) and (b). As shown in Figures 6(a) and (b), it was confirmed that the CuBi nanoparticles were composite particles in which Cu and Bi were separated into separate phases and Cu was coated with Bi. The average particle size of Cu in the CuBi nanoparticles was 38 nm.
[0056] (Preparation of positive electrode mixture) The positive electrode active material is the above CuBi nanoparticles, and the solid electrolyte is Pb 1.2 Sn 0.8 F4 Carbon powder was used as a conductive material and mixed to obtain a positive electrode mixture.
[0057] (Preparation of evaluation cell) 1cm 2 Pb in a ceramic mold 1.2 Sn 0.8 F 4 Weigh out 250 mg of the substance and apply a pressure of 1 ton / cm 2 A solid electrolyte layer was formed by pressing the electrode with a pressure of 1 ton / cm. 10 mg of the positive electrode mixture was placed on one side of the obtained solid electrolyte layer. 2 A positive electrode current collector (Pt foil) and a negative electrode current collector (Pt foil) were placed on the surfaces of the positive electrode active material layer and the solid electrolyte layer, respectively, and pressed at 4 ton / cm 2 In this way, 1 cm 2 During charging, the CuBi nanoparticles were fluorinated to become CuF x (0≦x≦2) and BiF 3 During charging, a defluorination reaction occurs in the region of the solid electrolyte layer on the negative electrode current collector side, and a negative electrode active material layer is formed by itself.
[0058] [Comparative Example 1] A pellet-type evaluation cell was produced in the same manner as in Example 1, except that Cu nanoparticles (average particle size 29 nm) were used as the positive electrode active material.
[0059] [Comparative Example 2] In the same manner as in the examples of JP 2018-063905 A, LaF was produced by a thermal plasma method. 3 A pellet-type evaluation cell was produced in the same manner as in Example 1, except that the Cu nanoparticles were used.
[0060] [evaluation] A charge-discharge test was carried out on the evaluation cell obtained in Example 1. The process in which a fluorination reaction occurred on the positive electrode side and a defluorination reaction occurred on the negative electrode side was regarded as charging, and the process in which a defluorination reaction occurred on the positive electrode side and a fluorination reaction occurred on the negative electrode side was regarded as discharging. The evaluation cell was placed in a sealed container, and charge-discharge was carried out while drawing a vacuum. The charge-discharge conditions were rate: 0.05C, voltage range: 1.3 to 0.3V (counter electrode Pb), and temperature: 60°C.
[0061] The results of TEM-EDX measurements of the fluorinated CuBi nanoparticles after the first charge are shown in Figure 7(a) and (b). As shown in Figure 7(a) and (b), the fluorinated CuBi nanoparticles are x (0 <x≦2)がBiF 3 It was confirmed that the composite particles were coated with CuF. x The average particle size of the Cu was 50 nm. That is, the average particle size of the Cu increased by about 1.3 times after the first charge. On the other hand, although not shown in the figure, the average particle size of the Cu used in Comparative Example 1 increased by about 3.1 times after the first charge. Thus, the Cu-based active material and the BiF 3 It was confirmed that the coexistence of these two substances can suppress the coarsening of particles.
[0062] The results of the charge / discharge test on the evaluation cell obtained in Example 1 are shown in Figure 8. Furthermore, the evaluation cells obtained in Comparative Examples 1 and 2 were charged and discharged under the same conditions. The results are shown in Figures 9 and 10. Furthermore, the results of the capacity obtained by the charge / discharge test are shown in Table 1.
[0063] [Table 1]
[0064] As shown in Figs. 8 to 10 and Table 1, it was confirmed that Example 1 had better capacity characteristics than Comparative Examples 1 and 2. During the initial charge in Fig. 8, from the start of charging to about 300 mAh / g, Bi in the CuBi nanoparticles was converted to BiF 3The reaction that results in [a certain state] occurs. On the other hand, from about 300 mAh / g to 950 mAh / g, Cu in the CuBi nanoparticles becomes CuF x (0 < x ≤ 2) and the reaction occurs. The charge capacity (650 mAh / g) associated with the fluorination of Cu was sufficiently large compared to Comparative Examples 1 and 2. On the other hand, it was confirmed that the defluorination reaction of BiF 3 did not occur during the first discharge. Also, in terms of discharge capacity, Example 1 was sufficiently large compared to Comparative Examples 1 and 2. Thus, it was confirmed that good capacity characteristics can be obtained by the coexistence of the Cu-based active material and BiF 3 .
Explanation of Reference Signs
[0065] 1 … Positive electrode active material layer 2 … Negative electrode active material layer 3 … Electrolyte layer 4 … Positive electrode current collector 5 … Negative electrode current collector 10 … Fluoride ion battery
Claims
1. Cu-based active material and BiF 3 and a positive electrode active material layer containing the The Cu-based active material is a fluoride ion battery represented by CuF x (0≦x≦2).
2. The positive electrode active material layer is formed by mixing the Cu-based active material with the BiF 3 10. The fluoride ion battery of claim 1 comprising composite particles coated with
3. 3. The fluoride ion battery according to claim 2, wherein a molar ratio of Cu to Bi (Cu / Bi) in the positive electrode active material layer is 1 or more and 3 or less.
4. A fluoride ion battery according to any one of claims 1 to 3, wherein x satisfies 0<x≦2.
5. The fluoride ion battery according to any one of claims 1 to 4, wherein the Cu-based active material has an average particle size of 100 nm or less.
6. a precursor layer forming step of forming a precursor layer containing a Cu-based active material and Bi; Fluoride ions are introduced into the precursor layer to form a Cu-based active material and a BiF 3 a positive electrode active material layer forming step of forming a positive electrode active material layer containing the having The method for producing a fluoride ion battery, wherein the Cu-based active material is represented by CuF x (0≦x≦2).
Citation Information
Patent Citations
Nano-composite battery electrode particles with changing properties
JP2017531907A
Fluoride ion battery
JP2018063905A
Positive electrode active material and fluoride ion battery
JP2019200852A